Ultrasensitive Immunosensor for Prostate-Specific Antigen Based on Enhanced Electrochemiluminescence by Vertically Ordered Mesoporous Silica-Nanochannel Film - Ma, Kai; Zheng, Yanyan; An, Lizhe; Liu, Jiyang (Frontiers in Chemistry, 2022)
Ultrasensitive and specific detection of prostate specific antigen (PSA) in complex biological samples is crucial for early diagnosis and treatment of prostate-related diseases. Immunoassay with simple sensing interface and ultrahigh sensitivity is highly desirable. Herein, a novel electroluminescence (ECL) immunosensing platform is demonstrated based on the equipment of vertically-ordered mesoporous silica-nanochannel films (VMSF) with PSA antibody, which is able to realize ultrasensitive detection of PSA in human serum. Through the electrochemically assisted self-assembly (EASA) method, VMSF is easily grown on indium tin oxide (ITO) electrode in a few seconds. Owing to large surface area and the negatively charged surface, VMSF nanochannels display strong electrostatic attraction to the positively charged ECL luminophores (tris(2,2-bipyridyl) dichlororuthenium (II), (Ru(bpy)32+), leading to two orders-of-magnitude enhancement of ECL emission compared with bare ITO electrode. The outer surface of VMSF is functionalized with reactive epoxy groups, which further allows covalent attachment of PSA antibody (Ab) on the entry of nanochannels. As the combination of PSA with Ab decreases ECL signal through hindering the mass transfer of ECL luminophores and co-reactors, the developed immunosensor can achieve ultrasensitive detection of PSA ranging from 1 pg mL-1-100 ng mL-1 with a limit of detection (LOD) of 0.1 pg mL-1. Considering the anti-fouling ability of VMSF, sensitive detection of PSA in human serum is also realized. The proposed nanochannel-based immunosensor may open up a new way for the facile development of universal immunosensing platform for rapid and ultrasensitive detection of disease markers.